Integrative taxonomy of Acrapex stem borers (Lepidoptera : Noctuidae : Apameini): combining morphology and Poisson Tree Process analyses - (:unkn) unknown (My University, 2014)
Ten morphologically similar species of Acrapex from eastern and south-eastern Africa belonging to the A. stygiata and A. albivena groups are reviewed. Six species are described as new: A. brunneella, A. mitiwa, A. mpika, A. salmona, A. sporobola and A. yakoba. The Poaceae host plants of eight species are recorded; four species, A. mitiwa. A. subalbissima, A. syscia and A. yakoba, were found developing exclusively on Imperata cylindrica (L.) Beauv., (Andropogoneae); two species, A. sporobola and A. salmona, on I. cylindrica and Sporobolus macranthelus Chiov. (Zoysieae); and A. albivena on I. cylindrica, Miscanthus capensis (Nees) Andersson (Andropogoneae) and Cymbopogon sp. (Andropogoneae). Acrapex stygiata larvae developed on M. capensis and Cymbopogon sp. The host plants of A. brunneella and A. mpika remain unknown. We also conducted molecular phylogenetics and molecular species delimitation analyses on a comprehensive sample of 49 specimens belonging to nine of the studied species. Molecular phylogenetics and molecular species delimitation analyses provided additional evidence of the validity of the six newly described species but also suggested a level of hidden biodiversity for one of them.
Keywords: African Research